2003
DOI: 10.1162/003465303772815745
|View full text |Cite
|
Sign up to set email alerts
|

The Macroeconomics of Happiness

Abstract: This paper shows that macroeconomic movements have strong effects on the happiness of nations. First, we find that there are clear microeconomic patterns in the psychological well-being levels of a quarter of a million randomly sampled Europeans and Americans from the 1970's to the 1990's. Happiness equations are monotonically increasing in income, and have a similar structure in different countries. Second, movements in reported well-being are correlated with changes in macroeconomic variables such as Gross D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
730
5
34

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,211 publications
(831 citation statements)
references
References 24 publications
51
730
5
34
Order By: Relevance
“…This large impact of insecurity on well-being is thought to account in part for the highly detrimental effects of aggregate unemployment on the average well-being of populations (Di Tella et al, 2003). Insecurity is naturally greater in a business downturn, but beyond that it is natural to look for ways of reducing insecurity perceptions.…”
Section: Introductionmentioning
confidence: 99%
“…This large impact of insecurity on well-being is thought to account in part for the highly detrimental effects of aggregate unemployment on the average well-being of populations (Di Tella et al, 2003). Insecurity is naturally greater in a business downturn, but beyond that it is natural to look for ways of reducing insecurity perceptions.…”
Section: Introductionmentioning
confidence: 99%
“…Already in 1974, Easterlin demonstrated that income and wealth, the benchmarks for social ranking during midlife, do not increase people's happiness (Easterlin, 1974), since people are trapped in a "hedonic treadmill" of rising subjective aspirations. More recent studies find mixed results, on the level of individual income as well as on the level of national wealth (Di Tella et al 2003;Alesina et al 2004;Frijters et al 2004;Dynan and Ravina, 2007;Clark et al 2008). Yet, there is little dispute that poverty marks an important objective threshold below which income seems to be decisive.…”
Section: Economic and Sociological Insightsmentioning
confidence: 99%
“…gali būti svarbūs laimės išgyvenimui (Frey 2008), paprastai jų poveikis gana mažas (Yang 2008). Tam prieštaraudami kai kurie analitikai (Di Tella et al 2003) mano, kad aukštas nedarbo lygis šalyje neigiamai veikia net dirbančių žmo-nių laimės pojūtį, nes jie ima labiau bijoti, kad praras darbą. Kita vertus, kai nedarbo lygis yra aukštas, bedarbiai nesijaučia tokie vieniši, o darbo netekimas neatrodo vien tik asmeninės nesėkmės išdava (Clark 2003).…”
Section: Nedarbas Neigiamos Emocijos Ir Beviltiškas Optimizmasunclassified